Raul Alcoseba and his impact on Chameleon Dance Theater - Cabling, Japhet Mari U. (Diliman, Quezon City U.P. College of Music, 2015)
This study aims to show the impact of Raul Alcoseba on Chameleon Dance Theater, also known as Chamelon, and its audiences during his years as the artistic director of the company. It focuses on finding the identity of Chameleon Dance Theater as contemporary dance group under the directorship of Raul Alcoseba and how his vision and works influenced the company and its members.
Thesis (Bachelor in Music) -- University of the Philippines, Diliman.
Keywords: Alcoseba, Raul; Chameleon Dance Theater